Saksi sa kasaysayan 2 [videorecording] the President on Trial - Estrada, Joseph; I Witness (Quezon City GMA Network, Inc., 2001)
The life of Joseph Estrada as President of the Philippines
GMA Network's Coverage of the Impeachment Trial and People Power II.
From the original (VHS # 131)
Keywords: President of the Philippines -- Estrada, Joseph